Non-Invasive Elimination of Superficial Tumours: a step forward - Amaral, Mariana Moura das Neves (2021)
Anaplastic thyroid carcinoma is a very rare subtype of thyroid carcinoma and one of the most lethal known malignancies, with a mean survival of 3-5 months. The poor prognosis is mainly due to its undifferentiated nature, inoperability and failing to respond to the typically used therapies for thyroid cancer. Photothermal Therapy (PTT) entails the use of light to increase the temperature of tissues, leading to hyperthermia-mediated cell death. Tumours are more susceptible to the generated heat as they are unable to dissipate it. By using targeted light-absorbing gold nanoparticles (AuNPs), able to transform the light energy into heat, it is possible to target the heat to a specific site, i.e., the tumour. The aim of this project was to formulate anaplastic thyroid carcinoma-targeted lightabsorbing AuNPs able to convert near-infrared light into heat, for PTT applicable to this malignancy. For this, different cores of AuNPs were synthetized and coated with polymeric material. Particle size, morphology and SPR band were determined. The optimized coated-AuNP core was then functionalized with three ligands to assess anaplastic thyroid carcinoma’s specificity. All formulations were tested in vitro for safety, efficacy and selectivity. Moreover, the formulations biodistribution and safety profiles were preliminarily assessed in vivo. The different formulations were deemed safe when not irradiated (<30% reduction in cell viability) and selective for anaplastic thyroid carcinoma. Holo-transferrin AuNP was the most cytotoxic when irradiated, promoting 22% of reduction in cell’s viability. Regarding the in vivo assessments, this formulation was demonstrated as being safe. Taking these all together, this novel formulation seems to be a viable approach for the treatment of anaplastic thyroid carcinoma, to assess in a very near future.